The effects of inhaled pimpinella peregrina essential oil on scopolamine-Induced memory impairment, anxiety, and depression in laboratory rats - Akbaba, Emel Aydın; Hritcu, Lucian; Doğan, Gülden; Hayta, Şükrü; Bağcı, Eyüp (My University, 2016)
In the present study, we identified the effects of inhaled Pimpinella peregrina essential oil (1 and 3 %, for 21 continuous days) on scopolamine-induced memory impairment, anxiety, and depression in laboratory rats. Y-maze and radial arm-maze tests were used for assessing memory processes. Also, the anxiety and depressive responses were studied by means of the elevated plus-maze and forced swimming tests. The scopolamine alone-treated rats exhibited the following: decrease of the spontaneous alternation percentage in Y-maze test, increase of the number of working and reference memory errors in radial arm-maze test, along with decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. Inhalation of the P. peregrina essential oil significantly improved memory formation and exhibited anxiolytic- and antidepressant-like effects in scopolamine-treated rats. Our results suggest that the P. peregrina essential oil inhalation ameliorates scopolamine-induced memory impairment, anxiety, and depression. Moreover, studies on the P. peregrina essential oil may open a new therapeutic window for the prevention of neurological abnormalities closely related to Alzheimer’s disease.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Compliance with Ethical Standards Rats were treated in accordance with the guidelines of the animal bioethics of the Act on Animal Experimentation and Animal Health and Welfare from Romania and all procedures were in compliance with Directive 2010/63/EU of the European Parliament and of the Council of 22 September 2010 on the protection of animals used for scientific purposes. This study was approved by the Committee on the Ethics of Animal Experiments of the Alexandru Ioan Cuza University of Iasi (Permit Number: 2192) and also, efforts were made to minimize animal suffering and to reduce the number of animals used.
Keywords: Pimpinella peregrina essential oil; Scopolamine; Memory; Anxiety; Alzheimer’s disease; Depression